Drug Resistance Mutations (DRMs) for Long-Acting Injectable Cabotegravir and Rilpivirine (CAB/RPV LAI) in the HIV-1 Subtype A6 Epidemic in Poland - Andrzej Załęski; Agnieszka Lembas; Tomasz Dyda; Joanna Osińska; Joanna Jabłońska; Justyna Stempkowska-Rejek; Justyna Orzechowska; Alicja Wiercińska-Drapało (Microorganisms)
HIV subtype A6 with the L74I polymorphism, which increases the risk of cabotegravir/rilpivirine treatment failure, causes more and more infections in Poland. In this multicenter, observational, cross-sectional study (2023–2024), we analyzed viral subtypes and drug-resistance mutations to drugs used for long-acting injectable antiretroviral treatment and pre-exposure prophylaxis. Among 357 people with HIV, 247 (69%) were Polish nationals, and 102 (29%) were from former Soviet Union countries. Of the 357 people included, 159 (45%) had subtype B, and 177 (50%) had subtype A6 infections, with 165 (87%) of the latter characterized by the L74I polymorphism. Subtype A6 was more frequent in women (66% vs. 46% in men, p < 0.05) and among people from former Soviet countries (77% vs. 39% in Polish nationals, p < 0.05). About 40% of people had either drug-resistance mutations for cabotegravir/rilpivirine or HIV A6 subtype with the L74I polymorphism; 4.5% had both of these conditions. Compared to subtype B infections, subtype A6 infections were characterized by more frequent major transmitted drug-resistance mutations for non-nucleoside reverse transcriptase inhibitors (8.5% vs. 1.9%, p = 0.007) and rilpivirine (5.1% vs. 0.6%, p = 0.016). Due to the frequent occurrence of the L74I polymorphism and drug-resistance mutations in HIV A6 subtype infection, about 40% of people with HIV in Poland may be at risk of long-acting injectable treatment failure.